Fisher investments on utilities - Gilliland, Theodore; Gilliland, Theodore; Teufel, Andrew S. (Hoboken, N.J. : Wiley, 2011)
"The definitive introduction to the Utilities sector Life requires basics such as electricity, water and gas. People put their trust in utility companies to deliver uninterrupted service of these goods. Readers can put their trust in Fisher Investments on Utilities to provide the tips and the tools necessary to understand and analyze investment opportunities within the global Utilities sector. The investing world is diverse and often times can be overwhelming to investors. Fisher Investments on Utilities simplifies things. The book describes how the Utilities sector works Details the investment universe of the Utilities sector segmented by industry Explains pertinent macroeconomic drivers and challenges facing companies in the Utilities sector Utilities-the stocks of companies delivering electric, water and gas-are a key part of a well-rounded, diversified global portfolio. Fisher Investments on Utilities can help readers to make informed investment decisions as to whether utilities are right for them."--
Includes index.
Includes bibliographical references and index.
Keywords: Public utilities -- United States -- Finance; Stocks -- United States; BUSINESS & ECONOMICS / Finance